Determinación de la concentración letal media cl50 producida por tridemorph en alevines de tilapia roja oreochromis sp - Morán Macay, Ángel Emilio (2012)
The aim of this study was to determine the median lethal concentration (LC50), produced by the fungicide Tridemorph by juvenile Tilapia (Oreochromis sp.), the same that is used to combat Black Sigatoka in banana plantations. The supplier of fingerlings for this study was Acuasol located in Canton Road Santa Rosa Port Jeli. Fingerlings were used 1,1 g, 10 animals placed in 4 liters of water in each aquarium glass, which were separately exposed to concentrations of 10, 15, 20, 25.30 and 35 ml of standard solution. The physical parameters were obtained by averaging, temperature: 26 0C, dissolved oxygen: 4.2 mg / l and a pH of 8.2. The tests were bioassays with static water. Readings were taken at 24, 48, 72, 96 hours of exposure in order to obtain the survival and parameters. The median lethal concentration (CL50) estimated with Probit Analysis of the graphical method. The average lethal concentration (CL50) in the three replicas of this research was to 0.020 mg / l. an average weight of 1.1 gr.